(untitled) (Conferencea, 2022)
Chronic cerebral ischaemia (CCI) is one of the leading causes of stroke. As a consequence of chronic circulatory disorders, an inflammatory response develops, characterised by the activation and release of cytokines, chemokines, adhesion molecules and proteolytic enzymes, which in turn contribute to damage to brain structures. HIM is worse among diabetic patients, leading to increased mortality and disability.